Efeito protetor da proteína anti-inflamatória Galectina-1 sobre o processo de uveíte induzida pelo inflamógeno lipopolissacarídeo - Zanon, Caroline de Freitas [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Inflammation is the main contributing factor for many eye disorders, and may lead to blindness and, in general, glucocorticoids are the drugs frequently administered. However, the side effects of these drugs limit their use. Endogenous protein galectin-1 (Gal-1) is able to control the process of apoptosis and transmigration of leukocytes, contributing to the homeostasis of inflammation. However, the expression of Gal-1 in normal and inflamed ocular tissues has been little studied. Investigate, in vivo, the expression and mechanism of action of endogenous protein Gal-1 in ocular tissues of rats in endotoxin-induced uveitis (EIU), and anti-inflammatory effect of administration of recombinant galectin-1 (rGal-1). Male rats (Rattus norvegicus) were anesthetized and inoculated in the right footpad with lipopolysaccharide (LPS) (1mg/kg) for developing uveitis, and after it divided into the following experimental groups (n=12/group): EIU 24 and 48h; EIU for 24h and treated intraperitoneally with rGal-1 (3μg/animal), 15 minutes after LPS. Blood was collected for detecting the percentage of positive cells for the adhesion molecules L-selectin (CD62L) and β2-integrin (CD11b) in polymorphonuclear leukocytes (PMNs), by flow cytometry. Inflammatory cells was quantified in aqueous humor (AqH) in the Neubauer chamber. After enucleation, the eyes were processed for histopathological analysis, dosage levels of MCP-1, IL-1β, TNF-α, IL-6 and IL-10 cytokine by panels Milliplex MAP and analysis of the expression of endogenous Gal-1 by immunohistochemistry and Western blotting. EIU 24h provoked expected signals of inflammation, including intense recruitment of neutrophils (Nɸs) in ocular tissues, AqH and blood, and release of proinflammatory cytokines. Treatment with rGal-1 attenuated the effects occurring in the EIU by inhibiting the infiltration of Nɸs in eye tissues and the AqH, percentage decreased of CD62L+ cells and, also, suppressing the ...

A inflamação é o principal fator contribuinte para inúmeras desordens oculares, podendo levar à cegueira e, em geral, são os glicocorticoides os medicamentos frequentemente administrados. No entanto, os efeitos adversos desses fármacos, limitam os seus usos. A proteína endógena galectina-1 (Gal-1) é capaz de controlar o processo de transmigração e apoptose dos leucócitos, contribuindo para a homeostase da reação inflamatória. No entanto, a expressão da Gal-1 em tecidos oculares normais e inflamados tem sido pouco estudada. Investigar a expressão e o mecanismo de ação da proteína endógena Gal-1 nos tecidos oculares de ratos na uveíte induzida por endotoxina (EIU) e o efeito anti-inflamatório da administração da galectina-1 recombinante (rGal-1). Ratos machos (Rattus norvegicus) foram anestesiados e inoculados na pata direita com lipopolissacarídeo (LPS) (1mg/Kg) para o desenvolvimento da uveíte e, após, divididos nos seguintes grupos experimentais (n=12/grupo): EIU 24 e 48h; EIU 24h e tratamento intraperitoneal com rGal-1 (3μg/animal), 15 minutos após o LPS. O sangue foi coletado para detecção da porcentagem de leucócitos polimorfonucleares positivos para as moléculas de adesão L-selectina (CD62L) e β2-integrina (CD11b), por citometria de fluxo. No humor aquoso (HA) foram quantificadas as células inflamatórias pela câmara de Neubauer. Os olhos, após enucleação, foram processados para análises histopatológicas, dosagens dos níveis das citocinas MCP-1, IL-1β, TNF-α, IL-6 e IL-10 por painéis Milliplex MAP e análises da expressão da Gal-1 endógena por imuno-histoquímica e Western blotting. A EIU 24h provocou sinais esperados de inflamação, incluindo intenso recrutamento de neutrófilos (Nɸs) nos tecidos oculares, HA e sangue, e liberação de citocinas pró-inflamatórias. O tratamento com rGal-1 atenuou os efeitos ocorridos na EIU por meio da inibição do infiltrado de Nɸs nos tecidos oculares ...
Keywords: Biologia molecular; Proteínas - Estrutura; Galectina 1; Moleculas de adesão celular; Leucócitos; Uveite; Endotoxina; Molecular biology